North Africa in transition the struggle for democracies and institutions - Fishman, Ben (Adelphi (Series) (International Institute for Strategic Studies), 2015)
This book is the first comprehensive examination of North Africa's political, security, and economic developments since the 2011 Arab Uprisings shook the Middle East. North Africa in Transition examines how the people and governments of North Africa have responded to the Arab uprisings that shook the region's politics in 2011. With individual chapters detailing key developments in Algeria, Libya, Morocco, and Tunisia, the authors bring together a wide range of expertise to assess how a previously under-explored and politically static region underwent bursts or energy, protests, and war. Two of the regimes were completely transformed and two adapted to survive. Of interest to North Africa specialists and scholars of democratic transitions, North Africa in Transition unravels the story of what has changed since 2011 and what security, political, and economic reforms are required to ensure progress and stability. The book argues that without the persistent and comprehensive development of key government institutions focused on creating jobs and providing security, the region risks future protests, terrorism or even revolution.